Association between the healthy eating index 2020 and heart failure among the U.S. middle-aged and older adults from NHANES 2005–2020: a cross-sectional study - Gu, Fangfang; Yu, Weiwei; Shu, Tian; Zhu, Yingwei (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to shed light on the correlation between Healthy Eating Index-2020 (HEI-2020) and heart failure (HF) in American adults aged 50 or above.MethodsData were from the National Health and Nutrition Examination Survey 2005–2020, encompassing 13,105 participants with an age of 50 or above. HEI-2020 score was utilized for rating the dietary quality. The link of HEI-2020 to HF was assessed via logistic regression, restricted cubic splines (RCS), generalized additive models (GAM), weighted quantile sum (WQS) regression, as well as quantile g-computation (Qgcomp) models.ResultsA negative association between HEI-2020 and HF risk was uncovered in middle-aged and older Americans (OR = 0.99, 95% CI: 0.98–1.00, p = 0.006). The highest quartile (Q4) exhibited a markedly lower HF risk than the lowest quartile (Q1) (OR = 0.70, 95% CI: 0.55–0.89, p = 0.004). RCS and GAM analyses demonstrated a linear dose–response relationship between HEI-2020 and HF. Finally, WQS regression and Qgcomp models revealed a beneficial combined influence of 13 dietary components on HF risk, with dairy and whole fruits emerging as the most influential.ConclusionElevated HEI-2020 scores are linked to decreased HF risks among Americans aged 50 or above, suggesting that adherence to the Dietary Guidelines for Americans can mitigate HF risk.